Determinants of purchasing intention on e-ticketing system among working adults in Malaysia / Nur Izzati Kamarulzaman - Kamarulzaman, Nur Izzati (Faculty of Business and Management, 2020)
With the evolution of technology, society has changed dramatically. Life was burdensome before the advent of modern technologies, and our daily tasks took too much of our energy. Technologies that play an important role in human life are creating enormous possibilities. Due to modern technologies, access to education, health, manufacturing, travel, etc. has been streamlined. Lives have improved significantly thanks to the comfort and flexibility offered by technology. There used to be a time when it would take most of the day to conduct a simple task such as buying an e-ticket. Therefore, the advancement of technology on e-ticketing system bring both benefits and disadvantages. The present study seeks to find about determinants of purchasing intention of e-ticketing system among working adults in Malaysia. The independent variables are user satisfaction, perceived usefulness, perceived ease of use and environmental concern. While the dependent variable is purchasing intention. A total of 250 questionnaires were keyed in and analysed by using SPSS software version 20. Furthermore, this research has used non-probability sampling which is the judgement sampling. All data were collected to obtain data about analysis or descriptive, correlation and regression analysis. In this study, findings show that there were three out of 4 variables that are significant which are perceived usefulness, perceived ease of use and environmental concern.